The Risk Factor for Mortality in COVID-19 Patients in Mohammad Hoesin Hospital, Palembang, Indonesia - Rico Januar Sitorus; Nyoman Yudi Antara; Rosyada Elviani; Zen Ahmad; Harun Hudari; Reymart V. Sangalang (Faculty of Public Health, Sriwijaya University, 2021)
World Health Organization (WHO) has declared the novel corona virus (COVID-19) as a pandemic due to its high transmission and the rapid spread of the COVID-19. Along these lines, there is a need for more research about risk factors that can affect the spread of COVID-19 and its fatality. Therefore, this study aims to analyze risk factors in patients who died from COVID-19 at the Mohammad Hoesin Hospital in Palembang, South Sumatra, Indonesia. This study used a cross-sectional approach. The data were collected from all patients who died with suspected, probable, and confirmed status until September 2020  Data on death due to COVID-19 were collected with suspect, probable, and confirmed status. The results showed that comorbidity became the most dominant factor (62.1%) with (OR Adj) 3.780 (1.000 - 3.168) after controlling for contact history with confirmed cases and sex. There were differences in the mean age and length of stay in patients with confirmed COVID-19 and not. Prevention of death in COVID-19 patients can be done by controlling comorbidities and contact history with positive cases of COVID-19.